2005
DOI: 10.1002/ejlt.200401113
|View full text |Cite
|
Sign up to set email alerts
|

Soybean germ oil inhibits oxidosqualene cyclase in 3T3 fibroblasts

Abstract: Soybean germ oil (SGO) could take an important place among nutraceuticals if the finding were confirmed that a daily intake of SGO helps to maintain a normal level of serum cholesterol. Adapting the rice milling technology to the soybean refining process, we achieved a rapid and efficient separation of soybean bran and cotyledon from the hypocotyle. Our soybean germ was no less than 95% hypocotyle. SGO obtained from it by typical hexane extraction was very rich in tocopherols (total content 4.35 g/kg) and phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“… 1 Currently, soybean germ is not commonly used for human consumption but is mainly used an ingredient in animal feeds. 2 It is rich in various nutrients including polyunsaturated fatty acids, protein, phytosterols, 3 tocopherols, 4 isoflavones and saponins. 5 In this regard, recent research has demonstrated that soybean germ protein could decrease weight due to body fat and increase the muscle weight of hind limbs in experimental animals, 6 while soybean germ oil could reduce blood cholesterol 7 and prevent UVB-induced cutaneous erythema.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Currently, soybean germ is not commonly used for human consumption but is mainly used an ingredient in animal feeds. 2 It is rich in various nutrients including polyunsaturated fatty acids, protein, phytosterols, 3 tocopherols, 4 isoflavones and saponins. 5 In this regard, recent research has demonstrated that soybean germ protein could decrease weight due to body fat and increase the muscle weight of hind limbs in experimental animals, 6 while soybean germ oil could reduce blood cholesterol 7 and prevent UVB-induced cutaneous erythema.…”
Section: Introductionmentioning
confidence: 99%